Does epigenetics have a role in age related macular degeneration and diabetic retinopathy? - S. Mohana Devi; I. Mahalaxmi; J. Kaavya; V. Chinnkulandhai; V. Balachandar (Genes and Diseases, 2021)
Epigenetic mechanisms play an important part in the regulation of gene expression and these alterations may induce long-term changes in gene function and metabolism. They have received extensive attention in bridging the gap between environmental exposures and disease development via their influence on gene expression. DNA methylation is the earliest discovered epigenetic alteration. In this review, we try to examine the role of DNA methylation and histone modification in Age related macular degeneration (AMD) and Diabetic Retinopathy (DR), its vascular complications and recent progress. Given the complex nature of AMD and DR, it is crucial to improve therapeutics which will greatly enhance the quality of life and reduce the burden for millions of patients living with these potentially blinding conditions.